Effect of the Skilled Worker Certification on the Sustainable Infrastructure Development - Nurin Pramadini; Inggar Septhia Irawaty; Ashar Saputra (Journal of the Civil Engineering Forum, 2017)
Infrastructure plays an important role in the occurring development process, in which the human resource is an important factor in it. This research was conducted in the work area of the Construction Training Agency Region II Surabaya Unit (Balai Pelatihan Konstruksi Wilayah II Surabaya). The data were collected by using questionnaire or questions list, which was given to the provider and the user of the skilled labor—consisted of 60 people of 30 certified skilled workers and 30 non-certified skilled workers. The data was processed by using SPSS. The result showed that the number of certified skilled workers that know the characteristic of sustainable infrastructure is higher when compared with the non-certified skilled workers. The average 95.4% of certified skilled workers know about the characteristic, while it’s 91.1% in the non-certified skilled workers. Certified workers that implement the characteristic of sustainable infrastructure is of 75.9% and 62.8% of noncertified workers do the aforementioned. According to the calculation, there is some influence between the knowledge of sustainable infrastructure characteristic and the project implementation, based on 57 from total 65 research variables.